INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN INOVATIF DI SEKOLAH DASAR - Mu?min Saud, Abdul (STKIP Subang, 2015)
The development of science, technology and information (science and technology) is very fast and globalization nowadays occur positive and negative impacts on people's lives, both individual and social life. The positive impact of the development of science and technology and the globalization of the labor market is opening opportunities in accordance with the needs of society and the state. While the negative impact is the changing values and norms of life that is often in contradiction with the norms and values of life that has existed in the community. In this context, education, especially primary education, plays a very important to preserve and protect the norms and positive life values that already exist in the society of a country from the negative effects of science and technology development and globalization. The education process is right and quality provided supplies and power to maintain the